General n-dimensional Tauberian problems with application to the Laplace- and Stieltjes transforms - Frennemo, Lennart (Mathematica Scandinavica, 2002)
A general theorem on the closure of translates in certain weighted spaces in R^n is proved and as a consequence a general n-dimensional Tauberian theorem. This is applied to the n-dimensional Laplace transform and to the one-dimensional Stieltjes- and Weierstrass transforms.